KORELASI KEPADATAN SAMBARAN PETIR AWAN KE TANAH DENGAN SUHU BASAH DAN CURAH HUJAN - A.Gani, Usman
Abstract: Indonesia archipelago, being situated along the equatorial line, is characterized, from view point of lightning activities, by relatively high ground flash densities compared with those of subtropical areas. So far, one of the parameters for indicating lightning activity is the Isokeraunic Level (IKL), whose figures describe the number of thunderdays during the period of one year, and they are normally represented in isoline on geographical map. However, by only knowing Isokeraunic Level (IKL) data one can not obtain sufficient picture on physical activity of lightning. In this study, the data on ground flash density, have been collected from the lightning observation station which are located near Subang, Kebumen, Tuban, and Panimbang. Those 4 (four) stations are using the so-called Time Difference and Direction (TDD) technique. Meanwhile, the climatic parameters data such as : wet-bulb temperature and precipitation, of the same period as of lightning observation data have been obtained from Meteorological and Geophysical Agency (BMG), Jakarta. The period of observation was done from November Ist , 1994 through February 28th, 1996. By applying the statistical regression analysis method on the observed data, namely : wet-bulb temperature, precipitation and ground flash density for certain locations in Java Island, i.e. : Bandung, Bogor, Jakarta, Madiun and Tasikmalaya, an empirical formula for estimating the ground flash density (Ng) as function of wet-bulb temperature (7) and Precipitation (P) has been derived. The formula is : Ng = -0,0063 + 0,0014P + 0,0031 T with the coefficient correlation R = 0.7128 where : Ng : ground flash density (flashes/month-km2) P : precipitation in mm T : wet-bulb temperature in Â°C The figure of coefficient correlation R is sufficiently high which, statistically, supports the hypothesis on significant correlation between ground flash density (Ng) and some climatic parameters especially wet-bulb temperature (7) and Precipitation (P).